3D printing of polymer matrix composites: A review and prospective. (1st February 2017) - Wang, Xin; Jiang, Man; Zhou, Zuowan; Gou, Jihua; Hui, David
Abstract: The use of 3D printing for rapid tooling and manufacturing has promised to produce components with complex geometries according to computer designs. Due to the intrinsically limited mechanical properties and functionalities of printed pure polymer parts, there is a critical need to develop printable polymer composites with high performance. 3D printing offers many advantages in the fabrication of composites, including high precision, cost effective and customized geometry. This article gives an overview on 3D printing techniques of polymer composite materials and the properties and performance of 3D printed composite parts as well as their potential applications in the fields of biomedical, electronics and aerospace engineering. Common 3D printing techniques such as fused deposition modeling, selective laser sintering, inkjet 3D printing, stereolithography, and 3D plotting are introduced. The formation methodology and the performance of particle-, fiber- and nanomaterial-reinforced polymer composites are emphasized. Finally, important limitations are identified to motivate the future research of 3D printing.